MODEL PENATAAN SARANA DAN PRASARANA LINGKUNGAN PERMUKIMAN DI BTN GRAHA ASERA DESA LAMONDOWO KECAMATAN ANDOWIA KABUPATEN KONAWE UTARA - Hendra Sakti (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
Abstract The general principle underlying the analysis of the capacity of road segments is that speed decreases as the current increases. The speed reduction due to addition of current is near constant at low and medium currents, but becomes greater at currents approaching capacity. Approaching capacity, a slight increase in flow will result in a large reduction in the speed of the performance of the Ambesea-Simpang Torobulu (Dermaga) Road Section decreased in service level in 2013, namely service level F with a Saturation Degree (DS) of 1.36 that has crossed the threshold recommended in the Indonesian Road Capacity Manual, which is 0.78 Based on the geometric characteristics of the road in the Indonesian Road Capacity Manual (MKJI 1997), the service level of the Ambesea-Simpang Torobulu Road Section (Pier) can be improved by increasing the width of the traffic lane from 6 meters to 11 meters, this is possible because the area of ​​land developed in the South Konawe Regency has only reached 49% of the targets planned in the South Konawe Regency Spatial Plan (RTRW), besides the Ambesea-Simpang Torobulu (Wharf) Road Section is also safe from landslide danger. Thus it is expected that in 2013 the level of service can be reduced to the level of service D.